"I Don't Have Time to Be Sad": Experiences and Perceptions of Sadness among Latina Mothers. Issue 2 (5th May 2021) - Pineros-Leano, María; Yao, Laura; Simonovich, Shannon D; Piñeros-Leaño, Natalia; Huang, Hsiang
Abstract: Maternal depression affects 10 percent to 17 percent of mothers in the United States. Women of color, particularly Latina women, may be at an elevated risk for adverse consequences of maternal depression. However, scant research addresses cultural experiences and perceptions of maternal depressive feelings. This study included interviews with 30 Latina immigrant mothers who were living in rural or small towns in the Midwest. Data were analyzed in Spanish using a thematic network approach. Authors identified three themes in relation to the experiences that Latina immigrant mothers described around sadness and depressive feelings: (1) normalization of feelings of sadness, (2) lack of social support that exacerbates feelings of isolation and sadness, and (3) traditional gender roles that compromise disclosure of feelings. The results from this study indicate that it is critical to increase support, provide culturally grounded discussions around mental health among Latina immigrant women, and continue these conversations beyond the perinatal period.